2017
DOI: 10.1177/0363546516680995
|View full text |Cite
|
Sign up to set email alerts
|

Suspensory Versus Aperture Fixation of a Quadrupled Hamstring Tendon Autograft in Anterior Cruciate Ligament Reconstruction: A Meta-analysis

Abstract: This meta-analysis demonstrated improved overall arthrometric stability and fewer graft ruptures using suspensory fixation compared with aperture fixation of a quadrupled hamstring tendon autograft in ACL reconstruction. There were no differences in IKDC, Lysholm, Lachman, and pivot-shift outcomes between suspensory and aperture fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
65
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 84 publications
9
65
0
2
Order By: Relevance
“…A recent meta-analysis by Browning et al. ( 2017 ) included 41 clinical level 1–4 studies comparing clinical outcome for patients treated with an ACLR with 4-strand hamstring autograft using either suspensory or aperture fixation. They found better arthrometric stability and fewer graft ruptures using suspensory compared with aperture fixation at a minimum of 2-year follow-up; however, they included graft fixation in the femur with cross-pins in the suspensory group.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis by Browning et al. ( 2017 ) included 41 clinical level 1–4 studies comparing clinical outcome for patients treated with an ACLR with 4-strand hamstring autograft using either suspensory or aperture fixation. They found better arthrometric stability and fewer graft ruptures using suspensory compared with aperture fixation at a minimum of 2-year follow-up; however, they included graft fixation in the femur with cross-pins in the suspensory group.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we hypothesized that an analysis of the comparison studies would provide some valuable insights into the ongoing debate. Browning et al had systematically reviewed ACLR using suspensory or aperture xation and found that the suspensory device engendered better knee stability and less graft failure (21). Recently, with the evolution of surgical instruments and techniques, suspensory devices are used in most all-inside ACLRs.…”
Section: Discussionmentioning
confidence: 99%
“…37 A recent meta-analysis by Browning et al revealed that there was significantly better knee stability in the suspensory fixation group compared with the aperture fixation group and the graft rupture rate was lower with suspensory fixation compared with aperture fixation. 38 The security of the graft is more reliant on tunnel wall integrity at aperture fixation than suspensory fixation. This might explain why there was better knee stability in the suspensory fixation group and reconfirmed that tendonto-bone healing was not always necessary for clinical stability of the knee joint.…”
Section: Discussionmentioning
confidence: 99%